Acquisition of Verb-Tenses among ESL Lecturers: an MDAB Pilot Study / Carolyn Soo Kum Yoke and Nor Haniza Hasan - Soo, Carolyn Kum Yoke; Hasan, Nor Haniza (2012)
This study examines the acquisition of Verb-Tenses by ESL lecturers using a prototype instrument called the T-Chronometer. The aim is to see to what extent the ESL lecturers are able to use the concept of tenses by means of the T-Chronometer for the purpose of teaching. This tool has been pilot tested on 21 ESL lecturers who taught the BEL011 Intensive English Course (MDAB Programme). They were given a pre and post test on verb-tenses after being exposed to the teaching method using the T-Chronometer tool. The results of the pre and post tests were compared for significant values using a T-test. The results measured were positive showing a significance in the use of the TChronometer for the teaching verb-tenses. It is therefore recommended that future studies be conducted for use among ESL learners.